2020
DOI: 10.15372/rgg2019085
|View full text |Cite
|
Sign up to set email alerts
|

The Lukoganskoe Au–Cu Skarn Deposit (Eastern Transbaikalia): Mineral Composition, Age, and Formation Conditions

Abstract: —The Lugokanskoe deposit is located in southeastern Transbaikalia and has been studied for a long time by many researchers. However, the type of its formation is still debatable. In this paper we study the mineral composition of ores by modern methods, recognize and describe the main gold mineral assemblages, and present detailed data on the chemical composition of native gold and sulfide minerals and their isotope composition. We have established that gold–pyrite–chalcopyrite–arsenopyrite and gold–bismuth par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Several types of ores are distinguished based on their mineral composition: magnetite (rather rare), scheelite-molybdenite (rare quartz veins in granodiorite-porphyries) and gold-sulfide (the most widespread type). Previous Ar-Ar studies showed that the formation of ore mineralization proceeded during the Late Jurassic time within the interval of 160-155 Ma; during the same time interval, the magmatic formations of the Shakhtama complex had widely occurred at the territory under investigation (the Ar-Ar age of biotite from granodiorite-porphyries of the Lugokan deposit is 154.7 ± 1.2 Ma) [14]. The Lugokan massif is composed mainly of granodiorite-porphyries of the second phase of the Shakhtama complex (Figure 2a,b).…”
Section: The Lugokan Depositmentioning
confidence: 92%
See 1 more Smart Citation
“…Several types of ores are distinguished based on their mineral composition: magnetite (rather rare), scheelite-molybdenite (rare quartz veins in granodiorite-porphyries) and gold-sulfide (the most widespread type). Previous Ar-Ar studies showed that the formation of ore mineralization proceeded during the Late Jurassic time within the interval of 160-155 Ma; during the same time interval, the magmatic formations of the Shakhtama complex had widely occurred at the territory under investigation (the Ar-Ar age of biotite from granodiorite-porphyries of the Lugokan deposit is 154.7 ± 1.2 Ma) [14]. The Lugokan massif is composed mainly of granodiorite-porphyries of the second phase of the Shakhtama complex (Figure 2a,b).…”
Section: The Lugokan Depositmentioning
confidence: 92%
“…The formation of the magmatic rocks of the Shakhtama complex proceeded during Late Jurassic time within the interval of 161-155 Ma [11]. Petrographic and petrochemical studies of the rocks of the Shakhtama complex carried out either and demonstrated that these rocks are metaluminious, magnesian, high-potassic granitoids [12][13][14].…”
Section: Geological Settingmentioning
confidence: 99%